The Foundations for Effective Indigenous Inclusion - Miller-Sabbioni, Christian; Goerke, Veronika; Downing, Mandy; van Leeuwen, Stephen (CRC TiME Limited, 2023)
This has been a short research initiative conducted by Curtin University for the Cooperative Research Centre for Transformations in Mining Economies (CRC TiME). The project aimed to articulate what constitutes ‘leading practice’ in post-mining and transitioning mine economies when Indigenous peoples are included in the activities and functions of mining. In this literature review ‘Foundations for Effective Indigenous Inclusion’ the objective was to identify amongst the existing literature ideas, procedures, protocols, processes, case studies, and evidence-base practices that would inform the establishment of a ‘leading practice’ relationship between Traditional Owners and CRC TiME. The aim was to provide CRC TiME with recommendations that support its intention to be a ‘leading practice’ facility that is founded on the principles of Indigenous inclusion and equity buttressed through co-designed research. This report has been written for adoption by CRC TiME staff and its partner organisations who engage with Traditional Owners through the institution of the CRC as well as for Traditional Owners to support their aspiration of what CRC TiME can and will do with them. This report also provides a comprehensive, although non-exhaustive, directory (Appendix 3) of Indigenous individuals, communities, businesses, and organisations that participants in CRC TiME may wish to engage with across the seven regionally place-based hubs which have been initially identified for development, and will be the focus for investment priorities and bringing together of stakeholders.